In utero exposure to di(2-ethylhexyl)phthalate suppresses blood glucose and leptin levels in the offspring of wild-type mice. (1st March 2019) - Hayashi, Yumi; Ito, Yuki; Naito, Hisao; Tamada, Hazuki; Yamagishi, Nozomi; Kondo, Takaaki; Ishikawa, Tetsuya; Gonzalez, Frank J.; Nakajima, Tamie
Abstract: Exposure of pregnant mice to di(2-ethylhexyl)phthalate (DEHP) induces maternal lipid malnutrition and decreases the number of live fetuses/pups. In this study, we aimed to clarify the relationship between maternal lipid malnutrition and the nutritional status of the neonatal, lactational, and adult offspring, as well as the role of peroxisome proliferator-activated receptor α (PPARα) in these relationships. Sv/129 wild-type (m PPARA ), Ppara -null, and PPARα -humanized (h PPARA ) mice were fed diets containing 0, 0.01, 0.05, or 0.1% DEHP in utero and/or during the lactational stage. The male offspring were killed on postnatal day 2 or 21, or after 11 weeks. Exposure to either 0.05% or 0.1% DEHP during both the in utero and lactational periods decreased serum glucose concentrations in 2-day-old m PPARA offspring. These dosages also decreased both serum and plasma leptin levels in both 2- and 21-day-old m PPARA offspring. In contrast, exposure to DEHP only during the lactational period did not decrease leptin levels, suggesting the importance of in utero exposure to DEHP. Exposure to 0.05% DEHP during the in utero and lactational periods also increased food consumption after weaning in both m PPARA and h PPARA mice; this was not observed in Ppara -null offspring. In conclusion, in utero exposure to DEHP induces neonatal serum glucose malnutrition via PPARα. DEHP also decreases serum and plasma leptin concentrations in offspring during the neonatal and weaning periods, in association with PPARα, which presumably results in increased of food consumption after weaning.